Correlation of Pradhana Deha Prakriti with Menstrual Signs and Symptoms During Menses in Mid-Age Healthy Women of Belgaum District: An Observational Study - Solankure, Kadambari; Gurav, Vinod; Sanu, Usharani; Bhagat, Nayana; Mall, Eksheka (International Journal of Pharmaceutical Investigation, 2025)
Background Prakriti is a unique concept, which exceptionally finds its presence in Ayurveda. It is the unique psychosomatic constitution of an individual, constituted on the basis of the innate qualities of the matruja beeja and pitruja beeja, along with the external factors present at the time of conception that determine the prakriti at that time itself. Having analyzed the lack of awareness as to the signs and symptoms of a good menstrual cycle, the enhancement of menstrual health was found to be crucial. Objectives To establish a correlation between women belonging to dwandwaja deha prakriti and the menstrual signs and symptoms experienced by them, during their menses. Materials and Methods A total number of 450 healthy volunteers, belonging to the age group 18 to 40 years, were randomly selected from Streeroga Prasuti OPD KLE Shri B. M. Kankanwadi Ayurveda Mahavidyalaya, Belagavi. The volunteers were first assessed by means of a validated prakriti questionnaire, and the same individuals were then also assessed for presence of menstrual signs and symptoms experienced by them during their menses. The obtained data was statistically analyzed to establish a correlation between prakriti of an individual and menstrual signs and symptoms experienced by them. Results Women with PK (Pitta-Kapha) and PV (Pitta-Vata) prakriti had higher reports of viscous blood and moderate flow, while those with VK (Vata-Kapha) and VP (Vata-Pitta) types of prakriti experienced dysmenorrhea. However, KV (Kapha-Vata) showed fewer issues overall, especially with loose stools and constipation. PV (Pitta-Vata) and PK (Pitta-Kapha) prakritis experienced higher rates of headaches and other symptoms, while VK (Vata-Kapha) and KV (Kapha-Vata) prakritis had lower occurrences of most symptoms, particularly nausea and vomiting. VP (Vata-Pitta) prakriti showed a notable frequency of headaches and other symptoms, but lower instances of vomiting and anorexia. Conclusion The study showed significant positive statistical correlation pertaining between prakriti and menstrual signs and symptoms.
Keywords: Deha prakriti; Menstrual signs and symptoms; Ayurveda; Prevention